Evaluating the variability of the modulus of elasticity of concrete through the use of different types and batches of aggregate - Vasconcellos,Alex Taira de (2021)
ABSTRACT The modulus of elasticity of concrete is often calculated as a function of the compressive strength, and as a deterministic value. However, variations in the aggregates properties may result in module values different than those estimated, which may lead to excessive deformation and eventual instability of the structure. In this work, the influence of the coarse aggregate batch variation on the variability of the modulus of elasticity of the concrete was investigated. Three different aggregate sources (one of granite origin and two of gneiss origin), three water/cement ratios (w/c) and five different batches of each aggregate were investigated. The compressive strength and static modulus of elasticity of the concretes were determined at 28 days. The analysis of variance (ANOVA) showed that the variable "batch" had a significant influence on the modulus of elasticity of the concrete, indicating that this property is a probabilistic variable indeed. The normality of the distribution of its values was attested, and values of characteristic modulus of elasticity were proposed, which were from 6 to 10% lower than the mean values. In addition, the use of gneissic aggregates led to modulus of elasticity values 30% higher than those of the concretes with granitic aggregates and equivalent compressive strengths, while the reduction of the w/c ratio from 0.71 to 0.46 increased the modulus of elasticity in about 5%.